Effect of Gold Nanoparticles on Luminescence Enhancement in Antibodies for TORCH Detection - Cuimei Chen; Ping Ding (Molecules)
Purposes: To explore the optimization method and application of Au-NP-enhanced luminol––H2O2 luminescence system in TORCH (TOX, RV, CMV, HSVI, and HSVII) detection. Method: 4.5 × 10−5 mmol/L gold nano solution was prepared with chloroauric acid as the reducing agent and trisodium citrate as the stabilizer. After curing for 3 days, Au NPs participate in the luminal–H2O2 luminescence system to detect TORCH antibodies and establish the cut off value. SPSS 18.0 software was used to analyze the TORCH antibodies detected by the nano-gold-enhanced luminol luminescence method and TORCH kit. Additionally, its detection performance is studied. Results: The results of a paired t-test for the absorbance values of samples with and without gold nanoparticles showed that there were statistically significant differences (p < 0.001) between the two methods in the detection of TOX, RV, CMV, HSVI, and HSVII. The luminescence values with the addition of gold nanoparticles were significantly higher than those without gold nanoparticles. Using the Au NP–luminol–H2O2 chemiluminescence method, 127 serum samples were tested for TORCH antibodies. The sensitivities were 84.6%, 83.3%, 90.9%, 85.7%, and 84.6%, while the specificities were 94.7%, 96.5%, 96.6%, 97.3%, and 95.6%, respectively. The sensitivity and specificity of the chemiluminescence method enhanced by gold nanoparticles are significantly improved compared to the chemiluminescence method without enhancers. Conclusions: Au NPs participate in the luminal–H2O2 luminescent system. The absorbance, sensitivity, and specificity of TORCH antibodies show that Au NPs can enhance the luminol–H2O2 luminescent system. Au NP–luminol–H2O2 luminescence system has broad application prospects in the detection of eugenics.